Post‐transcriptional regulation of transcript abundance by a conserved member of the tristetraprolin family in Candida albicans. Issue 6 (30th January 2015) - Wells, Melissa L.; Washington, Onica L.; Hicks, Stephanie N.; Nobile, Clarissa J.; Hartooni, Nairi; Wilson, Gerald M.; Zucconi, Beth E.; Huang, Weichun; Li, Leping; Fargo, David C.; Blackshear, Perry J.
Summary Members of the tristetraprolin (TTP) family of CCCH tandem zinc finger proteins bind to AU‐rich regions in target mRNAs, leading to their deadenylation and decay. Family members in Saccharomyces cerevisiae influence iron metabolism, whereas the single protein expressed in Schizosaccharomyces pombe, Zfs1, regulates cell–cell interactions. In the human pathogen Candida albicans, deep sequencing of mutants lacking the orthologous protein, Zfs1, revealed significant increases (> 1.5‐fold) in 156 transcripts. Of these, 113 (72%) contained at least one predicted TTP family member binding site in their 3′UTR, compared with only 3 of 56 (5%) down‐regulated transcripts. The zfs1Δ/Δ mutant was resistant to 3‐amino‐1, 2, 4‐triazole, perhaps because of increased expression of the potential target transcript encoded by HIS3. Sequences of the proteins encoded by the putative Zfs1 targets were highly conserved among other species within the fungal CTG clade, while the predicted Zfs1 binding sites in these mRNAs often 'disappeared' with increasing evolutionary distance from the parental species. C. albicans Zfs1 bound to the ideal mammalian TTP binding site with high affinity, and Zfs1 was associated with target transcripts after co‐immunoprecipitation. Thus, the biochemical activities of these proteins in fungi are highly conserved, but Zfs1‐like proteins may target different transcripts in each species.